1996
DOI: 10.1021/jp9602078
|View full text |Cite
|
Sign up to set email alerts
|

The LiHg(22Π3/2− ) System

Abstract: We report the determination of the complete LiHg shallow bound ground state potential curve by combination of laser-induced fluorescence spectroscopy of bound-bound transitions, photoassociation spectroscopy of bound-free transitions, and ab initio calculations. The results are evaluated by comparison of quantum mechanically simulated emission spectra with experimental data and used to describe spectroscopic features of the 2 2 Π 3/2 -X 2 Σ 1/2 + band as well as the photochemical formation Via excitation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Although photoassociation has been known at least since 1937 (127), the chemical implications of this process were described conceptually much later by Dubov et al (128). Photoassociation has been used for the spectroscopic study of excimer and exciplex molecules that have a repulsive ground state (129)(130)(131)(132)(133)(134)(135)(136)(137)(138) and more recently has gained interest because of its role in the generation of ultracold molecules (139)(140)(141)(142)(143)(144)(145)(146)(147)(148)(149)(150)(151)(152)(153), the real time observation of bimolecular reactions (124,154), and control of bimolecular encounters (99,126,155).…”
Section: Free-bound Bimolecular Reactions: Photoassociationmentioning
confidence: 99%
“…Although photoassociation has been known at least since 1937 (127), the chemical implications of this process were described conceptually much later by Dubov et al (128). Photoassociation has been used for the spectroscopic study of excimer and exciplex molecules that have a repulsive ground state (129)(130)(131)(132)(133)(134)(135)(136)(137)(138) and more recently has gained interest because of its role in the generation of ultracold molecules (139)(140)(141)(142)(143)(144)(145)(146)(147)(148)(149)(150)(151)(152)(153), the real time observation of bimolecular reactions (124,154), and control of bimolecular encounters (99,126,155).…”
Section: Free-bound Bimolecular Reactions: Photoassociationmentioning
confidence: 99%
“…2 we can see that the IPA potential agrees reasonably well with the potentials from molecular beam scattering studies (16,17), taking into account the moderate experimental resolution in molecular beam scattering studies. The agreement between the IPA potential and the ab initio one (15,11) is also good. The IPA potential appears to have steeper repulsive and attractive walls.…”
Section: Results and Spectral Analysismentioning
confidence: 65%
“…Most of the energy term values calculated using the IPA potential agree with the observed line positions within experimental accuracy. For comparison previously known potential energy curves from molecular beam scattering studies (16,17) and ab initio calculations (11,15) are also shown in Fig. 2.…”
Section: Results and Spectral Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Very little, however, is known about the interaction of alkali-metal atoms with mercury. The best studied system to date is Li+Hg, for which the results of bound-bound and bound-free fluorescence spectroscopy were corroborated by high-quality quantum chemical calculations of the lowest excited states [40,41]. High-quality relativistic studies of the CsHg system were performed by Polly et al [42].…”
Section: Introductionmentioning
confidence: 99%